2019
DOI: 10.3329/ajmbr.v5i1.41044
|View full text |Cite
|
Sign up to set email alerts
|

Production and compositional studies of milk in local Pabna cows of Bangladesh

Abstract: The Pabna is one of the potential local cattle breeds in Bangladesh regarding milk production and its nutritive quality. The aim of the study was to know the effect of lactation length, parity and management on production performance and nutritional/physiochemical composition of the milk of local Pabna cows. Besides the regular milking, 15 days’ interval test day milking was recorded from 12 local Pabna cows with different lactation period (up to fifth month of calving) from BLRI Regional Station, Baghabari du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 3 publications
5
3
6
Order By: Relevance
“…But higher CP content percentage of Para was reported by Kanak et al (2013) (8.9) than the present findings. CP content percentage of Napier (12.94) in the present study is in closer agreement with the findings of Talukder et al (2019). Sree and Vijayalakshmi (2018) reported much higher CP content percentage of Chanchi (36.16).…”
Section: Chemical Composition Of Roughage Samplessupporting
confidence: 92%
See 2 more Smart Citations
“…But higher CP content percentage of Para was reported by Kanak et al (2013) (8.9) than the present findings. CP content percentage of Napier (12.94) in the present study is in closer agreement with the findings of Talukder et al (2019). Sree and Vijayalakshmi (2018) reported much higher CP content percentage of Chanchi (36.16).…”
Section: Chemical Composition Of Roughage Samplessupporting
confidence: 92%
“…Alam et al (2015) and Kanak et al (2013) both reported the EE content of Para to be 2.65% and 2.10%, respectively which are lower than the present findings. Lower EE content of Napier (1.90%) was reported by Talukder et al (2019). Similar EE content of Chanchi (3.87%) and lower EE content of Chanchi (2.9%) were reported by Sree and Vijayalakshmi (2018) and Kumar et al (2016).…”
Section: Chemical Composition Of Roughage Samplessupporting
confidence: 81%
See 1 more Smart Citation
“…40,41 The average milk production of indigenous cattle ranged between 0.50 to 2.50 liters per day while 4.79 liter / day in Pabna variety. 42 Unique dairy cattle herd of different cross-bred are available in Baghabari region of Milk-Vita. The genetic admixture in dairy herd showed the combination of several breeds in which the frequency of Holstein-Friesian has the highest regarding predominant individual breed characteristics followed by Jersey and Sahiwal with local cows (mainly Pabna cattle).…”
Section: Pabna Variety Cattlementioning
confidence: 99%
“…Comparatively higher total solids (14.81% vs. 12.97) and fat (6.17% vs. 4.92%) have been reported in Pabna variety cows reared on station (BLRI) than rural community which might be due to concentrate supplement to cows maintained at BLRI station. 42 The physiological condition of the animals and quality of milk may be evaluated based on milk metabolites. Four 271…”
Section: Composition Of Milkmentioning
confidence: 99%